Accessing Ancestral Origin and Diversity Evolution by Net Divergence of an Ongoing Domestication Mediterranean Olive Tree Variety - Sales, Hélia; Šatović, Zlatko; Alves, Mara Lisa; Fevereiro, Pedro; Nunes, João; Vaz Patto, Maria Carlota (Frontiers in Plant Science, 2021)
Olea europaea ‘Galega vulgar’ variety is a blend of West and Central Mediterranean germplasm with cultivated-wild admixture characteristics. ‘Galega vulgar’ is known for its high rusticity and superior-quality olive oil, being the main Portuguese variety with high impact for bioeconomy. Nevertheless, it has been replaced by higher-yielding and more adapted to intensive production foreign varieties. To clarify the potential ancestral origin, genetic diversity evolution, and existing genetic relationships within the national heritage of ‘Galega vulgar’, 595 trees, belonging to ancient and centenary age groups and prospected among ten traditional production regions, were characterized using 14 SSR markers after variety validation by endocarp measurements. Ninety-five distinguishable genets were identified, revealing the presence of a reasonable amount of intra-genetic and morphological variability. A minimum spanning tree, depicting the complete genealogy of all identified genets, represented the ‘Galega vulgar’ intra-varietal diversity, with 94% of the trees showing only a two-allele difference from the most frequent genet (C001). Strong correlations between the number of differentiating alleles from C001, the clonal size, and their net divergence suggested an ancestral monoclonal origin of the ‘Galega vulgar’, with the most frequent genet identified as the most likely origin of all the genets and phenotypic diversification occurring through somatic mutations. Genetic erosion was detected through the loss of some allele combinations across time. This work highlights the need to recover the lost diversity in this traditional olive variety by including ancient private genets (associated with potential adaptation traits) in future breeding programs and investing in the protection of these valuable resources in situ by safeguarding the defined region of origin and dispersion of ‘Galega vulgar’. Furthermore, this approach proved useful on a highly diverse olive variety and thus applicable to other diverse varieties due either to their intermediate nature between different gene pools or to the presence of a mixture of cultivated and wild traits (as is the case of ‘Galega vulgar’).